Leveraging Business Principles to Improve Human Resource Management in the Public Sector in South Africa - Simon Matome Nkgapele; Phumlani Dlamkile; Sifiso Mofokeng (Research Synergy Foundation, 2025)
The South African public sector plays an important role in socio-economic development and Human Resource Management (HRM) is an important element to ensure the provision of effective services. Based on a qualitative approach and a huge dependence on secondary data, the study explored lessons learned from business management principles for improving HRM in the public sector in South Africa. The study focused on key areas such as leadership, talent acquisition, retention and remuneration, performance management, and employee development, and highlighted how adaptation of business management frameworks could improve these areas. The results show that the objectives and operational context of the public and business sectors are non-identical, but business HRM practices such as agile leadership, talent acquisition, retention, compensation and performance management, and employee development strategies can be tailored to the specific needs of the public sector. The study recommended the implementation of strategies such as efficient recruitment, performance-based incentives, and non-monetary benefits will address key challenges, improving services and enhancing public trust in government institutions.